Wide-temperature-range heat-resistant bi-component polyurethane heat-conducting structural adhesive for power battery PACK as well as preparation method and application of structural adhesive
By introducing a special silane structure and a ternary esterified structure of high EO modified polyol into the structural glue for power battery PACK, combining metal and non-metallic inorganic fillers, the problem of inability to take into account both the room temperature flexibility and high temperature heat resistance in the prior art is solved, and the excellent heat resistance and wide temperature range applicability of polyurethane thermally conductive structural glue is achieved.
Patent Information
- Application Number
- CN202411782728.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing structural adhesives for PACK power batteries cannot take into account both the flexibility of the normal temperature and the heat resistance of high temperatures, resulting in insufficient safety when used under high frequency or severe vibration conditions and under wide temperature conditions.
A wide temperature domain heat-resistant two-component polyurethane thermal conductivity structure glue is adopted to enhance the binding force of the resin and inorganic materials by introducing a special silane structure. The ternary esterification structure of high EO modified polyols and PO polyethers and bio-based polyols is used to form a micro-phase structure with strong molecular binding force. Combined with the synergistic action of metal and non-metallic inorganic fillers, the modulus and heat resistance of the polyurethane glue are regulated.
It achieves low modulus, high toughness and good bonding strength at room temperature, and maintains excellent heat resistance and wide temperature range applicability at high temperatures, significantly improving the safety of the power battery PACK under high temperature conditions.
Smart Images

Figure BDA0005173196000000091 
Figure BDA0005173196000000101 
Figure BDA0005173196000000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of adhesives, and specifically relates to a wide-temperature range heat-resistant two-component polyurethane thermally conductive structural adhesive for a power battery PACK, and a preparation method and application thereof. Background Art
[0002] With the rapid and high-quality development of the electric vehicle industry, the efficiency of electrification technology and industrial development has increased significantly. Power battery pack (PACK) technology has become a cutting-edge technology in automobile manufacturing, constantly pursuing improved thermal management efficiency, safe and compact structure, and lightweight. The research on high-performance adhesive material solutions is undoubtedly a key link in the high integration and diversified design of battery systems. The thermal conductive structural adhesive used between the battery cells and the battery cells, and between the battery cells and the shell / cooling system in the power battery PACK plays multiple functions such as bonding, heat conduction, temperature resistance, heat insulation, flame retardancy, and pressure and impact resistance. Its comprehensive performance in various external environments and working temperatures is particularly important.
[0003] It is worth noting that the special structural mode of the power battery PACK puts forward three major performance requirements for thermal conductive structural adhesives: the first is stable bonding performance, requiring a tensile bonding strength of at least 8Mpa at room temperature (Al ~ adhesive ~ AL / PET) and extremely low performance loss under 1000h of high temperature and high humidity aging; the second is good toughness and shock resistance, with a room temperature modulus of 100-500Mpa and a high elongation to ensure that the vehicle is not prone to stress cracking or bonding failure under long-term driving vibration conditions; the third is excellent temperature resistance, good adhesion tolerance under high temperature environment (50-60℃), deformation resistance, as low modulus loss as possible, and passing the cold and hot alternating impact test of ~40-80℃. These requirements are more prominent in the development of PACK structural solutions represented by CTP (Cell To PACK, canceling modules, combining cells with shells, reducing the use of end plates and partitions) and CTB (Cell To Body, directly combining cells with chassis) and the increase in the penetration rate of adhesive use.
[0004] Currently, due to the disadvantages of traditional epoxy resin adhesives being too high in modulus and prone to stress cracking, and organic silicone adhesives being low in bonding strength, polyurethane, which has excellent bonding strength and very flexible formula design, has become the preferred material for structural adhesives for PACK. Since thermally conductive structural adhesives generally contain a large amount of inorganic thermally conductive fillers, in order to obtain a certain elongation at break, it is generally necessary to ensure that the adhesive has sufficient soft segment content, which often results in a low softening point of the material. Once the temperature rises, the elastic modulus drops significantly. Similar limitations make it impossible for structural adhesives for power battery PACKs on the current market to take into account both room temperature flexibility and high temperature heat resistance.
[0005] Patent CN202211294531.7 discloses a two-component polyurethane adhesive for bonding thermal conductive structures of power batteries and its preparation method. The thermal conductivity of the polyurethane thermal conductive structural adhesive is 0.85-1.51W. By reducing the amount of thermal conductive filler and adding additional flame retardants, it has high bonding strength and medium-low elastic modulus to improve toughness and shock resistance. However, the polyester polyol used has good hydrophobicity but insufficient heat resistance, and the heat resistance performance index only mentions the bonding strength, elongation at break, modulus after curing at room temperature for 7 days, and the strength and toughness of the double 85 after high temperature and high humidity aging, without reflecting the high temperature modulus, heat resistance and cold and hot shock performance.
[0006] The invention patent with application number CN202410053666.7 discloses a high-strength and high-temperature resistant two-component polyurethane thermally conductive structural adhesive and its preparation method. By using terephthalate diisocyanate (TDI-100) and 4,4-diphenylmethane diisocyanate (MDI-100) monomers, multifunctional polyester polyols with good thermal stability, and nano-scale thermally conductive fillers, the obtained polyurethane adhesive has good molecular regularity and symmetry, thereby obtaining high hardness, high bonding strength of more than 12Mpa, and high bulk strength (>6Mpa) at high temperature (60°C). However, its A component uses a polyester polyol with higher rigidity, and the B component uses a small molecule polyester polyol modified highly active fully symmetrical isocyanate monomer. The rigidity of the colloidal chain segment is too strong, which will lead to excessively high modulus at room temperature and too low toughness, which greatly increases the risk of cracking and failure of the power battery PACK in a vibration environment, and the performance data does not reflect the toughness and modulus. On the other hand, although TDI-100 and MDI-100 can improve heat resistance, their high activity will significantly reduce the operating time and affect the practical application of polyurethane adhesive.
[0007] The invention patent with application number CN202211307083.X discloses a heat-resistant polyurethane thermally conductive structural adhesive and its preparation method. The thermal conductivity of the polyurethane thermally conductive structural adhesive is 1.90-2.30W. By introducing polyether-modified silane, the surface hydrophobicity, temperature resistance and flexibility are improved, and aromatic polyols are used to improve the strength, temperature resistance, acid and alkali resistance of the polyurethane structural adhesive. However, its heat resistance is insufficient, and the shear strength performance loss after 1000h of the double "85" heat and humidity resistance test is large, and the minimum loss is also more than 34%, and the risk of high temperature or aging failure is relatively high.
[0008] To sum up the above analysis, developing a polyurethane thermal conductive adhesive material with excellent adhesion, low modulus and high toughness, excellent resistance to moisture and heat aging, especially low modulus loss at high temperature, to improve the safety of power battery systems under high frequency or severe vibration conditions and wide temperature range conditions, is a technical problem that needs to be urgently solved in this field. Summary of the invention
[0009] In view of the deficiencies in the prior art, the present invention aims to provide a wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive for power battery PACK. The two-component polyurethane thermal conductive structural adhesive enhances the bonding force between the resin and the inorganic material and the bonding force between the colloid and the metal surface by introducing a special silane structure, thereby greatly improving its resistance to moisture and heat and high and low temperature aging performance; and utilizes the polarity difference of the ternary ester structure of high EO modified polyols, PO polyethers and bio-based polyols to make the polyurethane adhesive have a microphase structure with strong molecular binding force at high temperature, and cooperates with the synergistic effect of the combination of metal and non-metallic inorganic filler thermal conductive powder and isocyanate-based polyurethane prepolymer, so that its room temperature modulus can be regulated within a relatively low range, and the high temperature modulus is improved, thereby achieving a combination of low modulus with heat resistance and aging resistance, and improving the applicability of power battery PACK under wide temperature range conditions, and the process is simple and the storage is stable, which is suitable for the thermal conductive structure bonding of key components of power battery PACK.
[0010] Another object of the present invention is to provide a preparation method and application of such a wide temperature range heat-resistant two-component polyurethane thermally conductive structural adhesive for power battery PACK.
[0011] To achieve this object, the present invention adopts the following technical solutions:
[0012] In a first aspect, the present invention provides a wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive for a power battery PACK, which comprises a component A and a component B;
[0013] Wherein, component A is composed of the following raw materials in parts by weight:
[0014] 20-55 parts of bio-based polyol, for example, 21, 23, 25, 30, 35, 40, 45, 50 parts, etc.;
[0015] Polyol resin A 5-20 parts, for example 6, 7, 8, 9, 10, 12, 15, 16, 18, 19 parts, etc.;
[0016] Polyol resin B 30-60 parts, for example 31, 32, 35, 38, 40, 45, 50, 55, 58 parts, etc.;
[0017] 160-275 parts of thermally conductive filler, for example, 165, 170, 175, 180, 185, 190, 200, 210, 220, 230, 240, 250, 260, 270 parts, etc.;
[0018] 2 to 6 parts of thixotropic agent, for example, 2, 3, 4, 5, 6 parts, etc.;
[0019] Dewatering agent A 2.5-7.5 parts, for example 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7 parts, etc.;
[0020] 0.2-0.5 parts of catalyst, for example 0.3, 0.4, 0.5 parts, etc.;
[0021] In parts by weight, component B consists of the following raw materials:
[0022] 80-100 parts of isocyanate-terminated polyurethane prepolymer, for example, 85, 90, 95, 99 parts, etc.;
[0023] 200-320 parts of thermal conductive filler, for example, 210, 230, 250, 280, 300, 310 parts, etc.;
[0024] 0.4-5 parts of thixotropic agent, for example, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 parts, etc.;
[0025] Dewatering agent B 0.5-1.2 parts, for example 0.6, 0.7, 0.8, 0.9, 1.0, 1.1 parts, etc.;
[0026] 3.5 to 9.5 parts of coupling agent, for example, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9 parts, etc.;
[0027] The component A and the component B are mixed in a volume ratio of 1:(0.9-1.2), such as 1:1, 1:1.1, preferably 1:1.
[0028] In a specific embodiment, the hydroxyl value of the bio-based polyol is 100-300 mgKOH / g, for example, 150 mgKOH / g, 200 mgKOH / g, 250 mgKOH / g, etc.; the bio-based polyol includes one or a combination of at least two of refined castor oil, Sovermol 750, Sovermol 760, Sovermol 805, Sovermol 810, Sovermol 815, Sovermol 818 produced by BASF, DB oil, Polycin D-290, Polycin D265, Polycin M280 produced by Vertellus, more preferably refined castor oil, Sovermol 805 or Sovermol 815.
[0029] In a specific embodiment, the polyol resin A is a polyether polyol with a functionality of 2 to 3, such as 3, and a number average molecular weight of 300 to 700, such as 300, 400, 500, 600 or 700.
[0030] Preferably, the polyol B is a high EO bisphenol A modified diol obtained by adding ethylene oxide (EO) to bisphenol A or adding ethylene oxide and propylene oxide simultaneously; preferably, the high EO bisphenol A modified diol is any one of DGEBAEO-6, DGEBAEO-8 or DGEBAEO-10, or a combination of at least two of them.
[0031] Bisphenol A modified diol can improve the wettability of the resin composition to the filler and the substrate, thereby improving the bonding strength. In the present invention, in addition to the above effects, the use of high EO bisphenol A modified polyol, through the polarity difference of the tertiary esterification structure of high EO bisphenol A modified polyol and PO polyether and bio-based polyol, makes the polyurethane colloid containing a large amount of thermal conductive filler have a microphase structure with strong molecular binding force at high temperature, reduces its segment / molecule binding force at room temperature and increases its segment / molecule binding force at high temperature, so that it can obtain room temperature flexibility, impact resistance and high temperature heat resistance.
[0032] In a specific embodiment, the thermal conductive fillers in the A component and the B component have the same composition, and are composed of at least one of the metal compound type thermal conductive fillers with D50 ≤ 100 μm and non-metallic inorganic fillers. The metal compound type thermal conductive filler includes any one or a combination of at least two of aluminum hydroxide, aluminum oxide, aluminum nitride, zinc oxide or magnesium oxide; the non-metallic inorganic filler includes any one or a combination of at least two of 800 mesh heavy calcium carbonate, 1250 mesh heavy calcium carbonate, 2000 mesh heavy calcium carbonate, D50 of 5 μm silicon micropowder, D50 of 10 μm silicon micropowder, D50 of 15 μm silicon micropowder, D50 of 20 μm silicon micropowder. More preferably, the thermally conductive filler comprises aluminum hydroxide with a D50 of 40 to 60 μm, aluminum hydroxide with a D50 of 1 to 10 μm, and 1250 mesh heavy calcium carbonate / silicon powder with a D50 of 20 μm, and the mass ratio of the aluminum hydroxide with a D50 of 40 to 60 μm, the aluminum hydroxide with a D50 of 1 to 10 μm, and the heavy calcium carbonate / silicon powder is (1.5 to 2.5):(1 to 1.5):1, for example, 2:1:1, 2.5:1.5:1, etc.; it may also comprise aluminum hydroxide with a D50 of 10 to 20 μm and 1250 mesh heavy calcium carbonate / silicon powder with a D50 of 20 μm, and the mass ratio of the aluminum hydroxide with a D50 of 10 to 20 μm and the 1250 mesh heavy calcium carbonate / silicon powder is (2.5 to 4):1, for example, 3:1, 3.5:1, 4:1, etc.
[0033] In the present invention, the selection of metal compound type thermally conductive fillers enables the polyurethane thermally conductive structural adhesive to have a certain thermal conductivity coefficient, and the combination of metal compound type thermally conductive fillers and non-metallic inorganic fillers is largely used to cooperate with the resin to form a stable blended phase structure, affecting the thermal motion of molecules or chain segments and the modulus change of the colloid within a certain temperature range, thereby affecting the heat resistance of the polyurethane adhesive.
[0034] In a specific embodiment, the catalyst is a combination of at least one of an organic bismuth catalyst and a tertiary amine catalyst, wherein the organic bismuth catalyst is one or more of bismuth neodecanoate, bismuth laurate, bismuth isooctanoate, and bismuth cyclohexane; the tertiary amine catalyst is one or more of triethylenediamine, pentamethyldiethylenetriamine, methylimidazole, and A-1. More preferably, the catalyst is a combination of an organic bismuth catalyst and triethylenediamine, and the mass ratio is (4 to 9): 1. In the present invention, the catalyst can meet the adjustment of gel time and complete curing time according to customer use requirements.
[0035] In a specific embodiment, the dehydrating agent A is any one of 3A molecular sieve, 4A molecular sieve and 5A molecular sieve, or a combination of at least two thereof.
[0036] In a specific embodiment, the isocyanate-terminated polyurethane prepolymer is an isocyanate prepolymer obtained by reacting a polyol with an isocyanate.
[0037] In a specific embodiment, the polyol is one or a combination of at least two of PPG polyol and polyol resin B having a functionality of 2 to 3 and a number average molecular weight of 2000 to 6000.
[0038] In a specific embodiment, the isocyanate includes any one or a combination of at least two of 4,4'-diisocyanate diphenylmethane, 2,4'-diisocyanate diphenylmethane, carbodiimide-modified MDI, HMDI or HDI trimer.
[0039] Preferably, the isocyanate-terminated polyurethane prepolymer is prepared by the following method:
[0040] Add polyol and isocyanate in quantitative proportions in a reactor equipped with a stirrer, a thermometer and a nitrogen gas supply device, start stirring, and heat to 75-80°C for reaction under stirring conditions for 3-3.5 hours; after the reaction is completed, cool to 50-60°C and then discharge the material to obtain an isocyanate-terminated polyurethane prepolymer.
[0041] In a specific embodiment, the thixotropic agents in component A and component B are both thixotropic agents with a specific surface area of 80 to 200 m 2 / g of hydrophobic fumed silica.
[0042] In a specific embodiment, the dehydrating agent B is one or a combination of at least two of Additive TI, Additive OF, dehydrating agent PTSI and dehydrating agent BF-5.
[0043] In a specific embodiment, the coupling agent is at least one of an epoxy silane coupling agent, a vinyl silane coupling agent or an isocyanate silane coupling agent;
[0044] Preferably, the epoxysilane coupling agent comprises any one of γ-glycidyloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, 3-(2,3-epoxypropyl)-propyltrimethoxysilane and 3-(3,4-epoxypropyl)-propyltrimethoxysilane;
[0045] More preferably, the coupling agent is a composition of an epoxysilane coupling agent and 1,2-bis(trimethylsiloxy)ethane. Among them, a molecular structure of 1,2-bis(trimethylsiloxy)ethane in the preferred embodiment has 6 alkoxy groups, and the silanol formed after hydrolysis is more acidic and can form a stronger and less hydrolyzable covalent bond with the hydroxyl groups on the metal surface; combining it with an ordinary silane coupling agent can further enhance the bonding force between the resin and the inorganic material and the bonding force between the colloid and the metal surface. The mass ratio of the epoxysilane coupling agent to 1,2-bis(trimethylsiloxy)ethane is (2 to 2.5):1.
[0046] In a second aspect, the present invention provides a method for preparing a two-component polyurethane thermally conductive structural adhesive for a power battery PACK as described in the first aspect, wherein the preparation method comprises preparing component A and preparing component B;
[0047] 1) Preparation method of component A: put the formulated amount of bio-based polyol, polyol resin A, polyol resin B, catalyst, thixotropic agent, dehydrating agent A and thermal conductive filler into a double planetary stirring kettle in sequence, start vacuum degassing, use a high-speed disperser and a stirring paddle to stir for 40 minutes to 1.5 hours, and finally discharge the material to obtain component A;
[0048] 2) Preparation method of component B: put the isocyanate-terminated polyurethane prepolymer, coupling agent, dehydrating agent B, thixotropic agent and thermal conductive filler in a double planetary stirring kettle in the formula amount, start vacuum degassing, use a high-speed disperser and a stirring paddle to stir for 40 minutes to 1.5 hours, and finally discharge the material to obtain component B.
[0049] 3) The above-mentioned component A and component B are loaded into a hose or other container and mixed evenly in a volume ratio of 1:(0.9-1.2) to obtain a two-component polyurethane thermal conductive structural adhesive.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] 1) The two-component polyurethane thermal conductive structural adhesive provided by the present invention utilizes the polarity difference of the ternary ester structure of high-EO bisphenol A modified polyol, PO polyether and bio-based polyol to make the polyurethane adhesive have a microphase structure with strong molecular binding force at high temperature, and cooperates with the synergistic effect of the metal, non-metallic inorganic filler combined thermal conductive powder and isocyanate-based polyurethane prepolymer to obtain a microphase structure with high molecular binding force at high temperature, further restricts the relative movement of the soft segment at high temperature, reduces the modulus loss of the polyurethane adhesive at high temperature, effectively improves the heat resistance of the polyurethane adhesive, and at the same time satisfies the requirement that the modulus at room temperature can be adjusted within a lower range.
[0052] 2) The two-component polyurethane thermally conductive structural adhesive provided by the present invention introduces multi-functional alkoxysilanes that can form a stronger and more hydrolysis-resistant bond with the metal surface, thereby comprehensively improving the bonding strength between the resin and the inorganic material and the bonding strength between the colloid and the metal surface, so that the thermally conductive structural adhesive has good resistance to moisture and heat and resistance to cold and heat shock. After double "85" high temperature and high humidity aging for 1000 hours and -40 to 80°C alternating cold and heat shock for 1000 hours, the bonding strength retention rate is greater than 90%.
[0053] 3) The two-component polyurethane thermal conductive structural adhesive of the present invention has low modulus, high toughness and good bonding strength at room temperature of 25°C, elastic modulus <600MPa, elongation at break>20%, AL-PET-Al lap tensile shear strength>9Mpa, and elastic modulus>70Mpa at 60°C, so that the bonding performance, flexibility and heat resistance of the polyurethane adhesive are excellently balanced, and it has wide temperature tolerance, which can reduce the risk of PACK components being damaged due to long-term or severe high-frequency vibration during the use of electric vehicles, and better improve the safety of PACK in high-temperature working environments. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below by specific implementation methods. However, those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0055] The following examples do not specify specific experimental methods, but are generally based on the conditions recommended by the industry and equipment manufacturers in the field. Unless otherwise specified, all raw material usage ratios are calculated by weight.
[0056] The detailed information of the raw materials involved in the specific implementation method is shown in Table 1:
[0057] Table 1
[0058]
[0059]
[0060]
[0061] The amounts of raw materials involved in the two-component polyurethane thermal conductive structural adhesive component A and component B described in the examples and comparative examples are listed in Table 2:
[0062] Table 2
[0063]
[0064]
[0065] Example 1
[0066] A wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive, comprising component A and component B.
[0067] Among them, the bio-based polyol in component A is refined castor oil, polyol resin A is polypropylene glycol 4, polyol resin B is bisphenol A modified diol 2, dehydrating agent A is 3A molecular sieve, and the catalyst is a combination of bismuth isooctanoate and triethylenediamine, with a mass ratio of 9:1.
[0068] The isocyanate-terminated polyurethane prepolymer in component B is prepared from polypropylene glycol 2 and diphenylmethane diisocyanate as raw materials. The specific preparation method is: polypropylene glycol 2 and diphenylmethane diisocyanate with a mass ratio of 1:2 are added in sequence to a reactor equipped with a stirrer, a thermometer and a nitrogen gas supply device, stirring is started, and the reaction is heated to 80°C under stirring conditions for 3 hours; after the reaction is completed, the temperature is lowered to 50°C and the material is discharged to obtain the isocyanate-terminated polyurethane prepolymer.
[0069] The dehydrating agent B in component B is a dehydrating agent of Additive TI, and a coupling agent of KH560 and 1,2-bis(trimethylsilyloxy)ethane, with a mass ratio of 2:1.
[0070] The thermal conductive filler in component A and component B is a combination of aluminum hydroxide 1 and 1250 mesh heavy calcium carbonate, with a mass ratio of 2.5:1, and the thixotropic agent is fumed silica R202.
[0071] A method for preparing the above-mentioned wide temperature range heat-resistant two-component polyurethane thermally conductive structural adhesive comprises the following steps:
[0072] 1) Preparation of component A: The formulated amount of bio-based polyol, polyol resin A, polyol resin B, catalyst, thixotropic agent, dehydrating agent A and thermal conductive filler are sequentially put into a double planetary stirring kettle, vacuum degassing is turned on, and stirring is carried out for 1 hour using a high-speed disperser and a stirring paddle to finally obtain component A.
[0073] 2) Preparation of component B: Put the formulated amount of isocyanate-terminated polyurethane prepolymer, coupling agent, dehydrating agent B, thixotropic agent and thermal conductive filler into a double planetary stirring kettle in sequence, start vacuum degassing, use a high-speed disperser and a stirring paddle to stir for 1 hour, and finally discharge the material to obtain component B.
[0074] 3) Mix component A and component B in a volume ratio of 1:1 and then use.
[0075] Example 2
[0076] A wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive, comprising component A and component B.
[0077] Among them, the bio-based polyol in component A is Sovermol 805, the polyol resin A is polypropylene glycol 4, the polyol resin B is bisphenol A modified diol 2, the dehydrating agent A is 3A molecular sieve, and the catalyst is a combination of bismuth isooctanoate and triethylenediamine, with a mass ratio of 9:1.
[0078] The isocyanate-terminated polyurethane prepolymer in component B is prepared from bisphenol A modified diol 3, polypropylene glycol 1 and carbodiimide modified MDI as raw materials, and the mass ratio of bisphenol A modified diol 3, polypropylene glycol 1 and carbodiimide modified MDI is 3:1:8.6. The preparation method is the same as that in Example 1.
[0079] The dehydrating agent B in component B is a dehydrating agent of Additive TI, and a coupling agent of KH560 and 1,2-bis(trimethylsilyloxy)ethane, with a mass ratio of 2:1.
[0080] The thermal conductive fillers in component A and component B are both a composition of aluminum hydroxide 2, aluminum hydroxide 3 and 1250 mesh heavy calcium carbonate, with a mass ratio of 1.5:1:1, and the thixotropic agent is fumed silica R202.
[0081] The preparation method is the same as Example 1.
[0082] Example 3
[0083] A wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive, comprising component A and component B.
[0084] Among them, the bio-based polyol in component A is refined castor oil, polyol resin A is polypropylene glycol 4, polyol resin B is bisphenol A modified diol 3, dehydrating agent A is 5A molecular sieve, and the catalyst is a combination of bismuth neodecanoate and triethylenediamine, with a mass ratio of 4:1.
[0085] The isocyanate-terminated polyurethane prepolymer in component B is prepared from polypropylene glycol 2 and HMDI as raw materials, and the mass ratio of polypropylene glycol 2 to HMDI is 1:2. The preparation method is the same as that in Example 1.
[0086] The dehydrating agent B in component B is a dehydrating agent of Additive TI, and a coupling agent of KH560 and 1,2-bis(trimethylsilyloxy)ethane, with a mass ratio of 2.5:1.
[0087] The thermal conductive fillers in component A and component B are both a composition of aluminum hydroxide 2, aluminum hydroxide 3 and 20 μm silicon powder, with a mass ratio of 2.5:1.5:1, and the thixotropic agent is fumed silica R974.
[0088] Example 4
[0089] A wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive, comprising component A and component B.
[0090] Among them, the bio-based polyol in component A is refined castor oil, polyol resin A is polypropylene glycol 5, polyol resin B is bisphenol A modified diol 2, dehydrating agent A is 5A molecular sieve, and the catalyst is a combination of bismuth neodecanoate and triethylenediamine, with a mass ratio of 8:1.
[0091] The isocyanate-terminated polyurethane prepolymer in component B is the same as that in Example 1.
[0092] The dehydrating agent B in component B is Additive OF, and the coupling agent is a combination of KH560 and 1,2-bis(trimethylsilyloxy)ethane, with a mass ratio of 2.2:1.
[0093] The thermal conductive filler in component A and component B is a composition of aluminum hydroxide 1 and silicon micropowder with a D50 of 20 μm, with a mass ratio of 4:1. The thixotropic agent in component A and component B is the same as that in Example 1.
[0094] Example 5
[0095] A wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive, comprising component A and component B.
[0096] Among them, the bio-based polyol in component A is refined castor oil, polyol resin A is polypropylene glycol 6, polyol resin B is bisphenol A modified diol 4, dehydrating agent A is 3A molecular sieve, and the catalyst is a combination of bismuth isooctanoate and triethylenediamine, with a mass ratio of 9:1.
[0097] The isocyanate-terminated polyurethane prepolymer in component B is the same as that in Example 2.
[0098] The dehydrating agent B in component B is a dehydrating agent of Additive TI, and a coupling agent of KH560 and 1,2-bis(trimethylsilyloxy)ethane, with a mass ratio of 2:1.
[0099] The thermal conductive fillers in component A and component B are the same as those in Example 2, and the thixotropic agents are both fumed silica R974.
[0100] Comparative Example 1
[0101] The only difference between this comparative example and Example 1 is that the polyol resin B in the preparation raw material of component A is replaced by polypropylene glycol 3 of the same mass.
[0102] Comparative Example 2
[0103] The difference between this comparative example and Example 2 is that the polyol resin B in the preparation raw material of component A uses bisphenol A modified diol 1; the bisphenol A modified diol 3 in the preparation raw material of the isocyanate-terminated polyurethane prepolymer in component B is replaced by bisphenol A modified diol 5.
[0104] Comparative Example 3
[0105] The only difference between this comparative example and Example 3 is that the polyol resin B in the preparation raw material of component A uses bisphenol A modified diol 5.
[0106] Comparative Example 4
[0107] The only difference between this comparative example and Example 4 is that the aluminum hydroxide 1 in the thermal conductive filler in the raw materials for preparing components A and B is replaced by aluminum hydroxide 4. The other components, amounts and preparation methods are the same as those in Example 4.
[0108] Comparative Example 5
[0109] The difference between this comparative example and Example 5 is that the weight percentage of the coupling agent in the raw material for preparing component B is 0.5 parts. The other components, dosages and preparation methods are the same as those in Example 4.
[0110] Performance Test:
[0111] (1) Thermal conductivity: The test is carried out in accordance with the standard "ASTM D5470-2012 Standard Test Method for Thermal Transfer Characteristics of Thermally Conductive Electrical Insulating Materials"; the test equipment is Xiangyi DRL-Ⅲ Thermal Conductivity Tester (heat flow method).
[0112] (2) Tensile shear strength: The test was conducted in accordance with the standard "GB / T 7124-2008 Determination of tensile shear strength of adhesives". 3003 aluminum alloy with a specification of 25mm×100mm×2mm and 100μm PET film were used as the test substrates. The AL-PET-AL sandwich structure was used for overlap. The adhesive layer area was 12.5mm×25mm; the thickness was 0.2mm; the aluminum material was wiped with alcohol to remove the surface oil in advance, and the PET was not specially surface treated. The test equipment was a microcomputer-controlled universal test tensile machine.
[0113] (3) DMA modulus: The test was conducted in accordance with the American standard ASTM E1640-13. Samples with dimensions between 1 mm × 5 mm × 20 mm and 1 mm × 10 mm × 50 mm were prepared, and a tensile fixture was used. The test frequency was 1 Hz, the test temperature range was -40°C to 85°C, the heating rate was 1°C / min, and the amplitude was 0.1% of the sample clamping length.
[0114] (4) Tensile strength and elongation at break: Tested in accordance with GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber. The test equipment is a microcomputer-controlled universal testing tensile machine.
[0115] (5) High temperature and high humidity aging test: The test was carried out in accordance with the standard "GB / T 2423.3 Environmental testing Part 2: Test method Test Cab: Constant humidity test". The samples cured at 25°C for 7 days were placed in a constant temperature and humidity chamber with an experimental temperature of 85°C and a humidity of 85rh%. After 1000h aging, the samples were tested for bonding strength, tensile strength and elongation at break.
[0116] (6) Thermal shock test: The test was conducted in accordance with GB / T 2423.22 Environmental testing Part 2: Test method Test N: Temperature change. The samples cured at 25°C for 7 days were placed in a thermal shock test chamber, alternating between -40°C and 80°C for 1 hour each, for a total of 500 cycles, and a total of 1000 hours to test the bonding strength, tensile strength and elongation at break of the samples.
[0117] (7) Flame retardant properties are tested in accordance with the US ANSI / UL-94-1985 standard.
[0118] According to the above test method, the two-component thermally conductive structural adhesives provided in Examples 1 to 5 and Comparative Examples 1 to 5 were tested after curing for 7 days at 25° C. and 50 rh%. The test results are shown in Table 3:
[0119] Table 3
[0120]
[0121]
[0122] Note: The tensile shear strength retention rate (%) in the table refers to the percentage of the tensile shear strength of the sample after a certain test condition and time to the initial tensile shear strength of the sample.
[0123] As can be seen from the above table, the thermal conductivity of the two-component polyurethane heat-conductive structural adhesive of the present invention can reach 0.8-1.5W, and it has good thermal conductivity; the bonding strength is greater than 9Mpa, the room temperature modulus is 366-598Mpa, and the elongation at break is 21.5-36.5%. Under the premise of ensuring good structural bonding performance, it has a low room temperature modulus and excellent flexibility, and is expected to significantly reduce the risk of bonding failure of power battery PACK under long-term vibration conditions. More noteworthy is that the polyurethane heat-conductive structural adhesive of the present invention has excellent heat resistance, and the modulus can reach more than 70Mpa at a high temperature of 60°C, which can reduce the modulus loss of the power battery PACK in a wide temperature range from room temperature to high temperature, and ensure dimensional stability. Moreover, under a particularly preferred combination of thermally conductive fillers, catalysts and coupling agents, by further limiting the type and EO content of the bisphenol A-modified diol, the microphase separation structure of the hard segment and the soft segment can be further regulated, the molecular binding force can be increased, and the relative movement of the soft segment at high temperature can be restricted, so that it can achieve excellent heat resistance and wide temperature range applicability at a lower room temperature modulus.
[0124] By comparing the test data of Examples 1 to 3 and Comparative Examples 1 to 3, it can be found that the use of high-EO bisphenol A modified diol in the thermally conductive structural adhesive system has a significant effect on improving the high temperature resistance of the thermally conductive structural adhesive, and can achieve a high temperature modulus of about 80 MPa on the basis of low room temperature modulus and good toughness. Further comparison of Example 1 and Comparative Example 1 shows that when general PO polyether is used in component A of the polyurethane thermal conductive structural adhesive, the 60°C modulus of the obtained polyurethane thermal conductive structural adhesive drops to less than 30Mpa, and the high temperature and high humidity aging ability decreases, and the strength retention rate is less than 70%; further comparison of Example 2 and Comparative Example 2, Example 3 and Comparative Example 3 shows that when component A of the polyurethane thermal conductive structural adhesive or the entire system uses low EO bisphenol A modified diol or PO type bisphenol A modified diol, although the room temperature properties of the thermal conductive structural adhesive such as room temperature modulus and tensile shear strength do not change much, its high temperature tolerance is significantly reduced, wherein the 60°C modulus of the thermal conductive structural adhesive in Comparative Example 2 and Comparative Example 3 is respectively reduced by 44% and 52% compared with the corresponding embodiment, and the high temperature and high humidity resistance and cold and hot shock performance are also significantly reduced. The polyurethane thermal conductive structural adhesive system provided by the present invention adopts thermal conductive fillers with particle sizes within a certain range and high EO bisphenol A modified diols and other components to achieve a good interaction between the two-component system resin, additives and fillers. By comparing the test data of Example 4 and Comparative Example 4, it can be seen that when the particle size of the metal thermal conductive filler in the system is too large, the thermal conductivity, bonding strength and tensile properties will decrease. Further comparison of the performance data of Example 5 and Comparative Example 5 shows that when the component content of the coupling agent is not within the range specified by the present invention, it will lead to the loss of heat resistance and aging resistance, making it difficult to achieve an excellent balance in the various properties of the final polyurethane thermal conductive structural adhesive.
[0125] The applicant declares that the present invention illustrates the two-component polyurethane thermal conductive structural adhesive and its preparation method through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A wide temperature range heat-resistant two-component polyurethane thermal conductive structural adhesive for power battery PACK, characterized in that: Including component A and component B: Wherein, component A is composed of the following in parts by weight: In parts by weight, component B consists of the following: The A component and the B component are mixed in a volume ratio of 1:(0.9-1.2).
2. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The bio-based polyol has a hydroxyl value of 100-300 mgKOH / g, and preferably includes one or a combination of at least two of refined castor oil, Sovermol 750, Sovermol 760, Sovermol 805, Sovermol 810, Sovermol 815, Sovermol 818, DB oil, Polycin D-290, Polycin D265, Polycin M280, more preferably refined castor oil, Sovermol 805 or Sovermol 815.
3. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The polyol resin A is selected from polyether polyols with a functionality of 2 to 3 and a number average molecular weight of 300 to 700; and / or The polyol resin B is a high EO bisphenol A modified diol obtained by adding ethylene oxide (EO) to bisphenol A or adding ethylene oxide and propylene oxide at the same time; preferably, the high EO bisphenol A modified diol is any one of DGEBAEO-6, DGEBAEO-8 or DGEBAEO-10, or a combination of at least two of them.
4. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The thermally conductive fillers in the A component and the B component have the same composition, and are composed of at least one of the metal compound thermally conductive fillers with D50≤100 μm and a non-metallic inorganic filler; Preferably, the metal compound type thermally conductive filler comprises any one of aluminum hydroxide, aluminum oxide, aluminum nitride, zinc oxide or magnesium oxide, or a combination of at least two thereof; and / or The non-metallic inorganic filler includes any one of 800 mesh heavy calcium carbonate, 1250 mesh heavy calcium carbonate, 2000 mesh heavy calcium carbonate, D50 of 5 μm silicon micropowder, D50 of 10 μm silicon micropowder, D50 of 15 μm silicon micropowder, D50 of 20 μm silicon micropowder, or a combination of at least two thereof; More preferably, the metal compound type thermal conductive filler comprises aluminum hydroxide with a D50 of 40 to 60 μm, aluminum hydroxide with a D50 of 1 to 10 μm, and 1250 mesh heavy calcium carbonate / silicon powder with a D50 of 20 μm; and / or The metal compound type thermal conductive filler comprises aluminum hydroxide with a D50 of 10 to 20 μm and 1250 mesh heavy calcium carbonate / silicon powder with a D50 of 20 μm; Further preferably, the mass ratio of the aluminum hydroxide with a D50 of 40 to 60 μm, the aluminum hydroxide with a D50 of 1 to 10 μm and the heavy calcium carbonate of 1250 mesh / silicon powder with a D50 of 20 μm is (1.5 to 2.5):(1 to 1.5):1; and / or The mass ratio of the aluminum hydroxide with a D50 of 10 to 20 μm and the 1250 mesh heavy calcium carbonate / silicon micropowder with a D50 of 20 μm is (2.5 to 4):
1.
5. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The isocyanate-terminated polyurethane prepolymer is an isocyanate prepolymer obtained by the reaction of polyol and isocyanate; Preferably, the polyol is one or a combination of at least two of a polyol having a functionality of 2 to 3 and a number average molecular weight of 2000 to 6000 and the polyol resin B; and / or The isocyanate includes any one of 4,4'-diisocyanate diphenylmethane, 2,4'-diisocyanate diphenylmethane, carbodiimide-modified MDI, HMDI or HDI trimer, or a combination of at least two thereof.
6. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The catalyst is a combination of at least one of an organic bismuth catalyst and a tertiary amine catalyst; Preferably, the organic bismuth catalyst is one or more of bismuth neodecanoate, bismuth laurate, bismuth isooctanoate, and bismuth cyclohexaneate; and / or The tertiary amine catalyst is one or more of triethylenediamine, pentamethyldiethylenetriamine, methylimidazole, and A-1; More preferably, the catalyst is a composition of an organic bismuth catalyst and triethylenediamine, and the mass ratio of the organic bismuth catalyst to triethylenediamine is (4-9):
1.
7. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The coupling agent is at least one of an epoxy silane coupling agent, a vinyl silane coupling agent or an isocyanate silane coupling agent; Preferably, the epoxysilane coupling agent comprises any one of γ-glycidyloxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane, 3-(2,3-epoxypropyl)-propyltrimethoxysilane and 3-(3,4-epoxypropyl)-propyltrimethoxysilane; More preferably, the coupling agent is a composition of an epoxysilane coupling agent and 1,2-bis(trimethylsiloxy)ethane, and the mass ratio of the epoxysilane coupling agent to 1,2-bis(trimethylsiloxy)ethane is (2-2.5):
1.
8. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The dehydrating agent A is any one of 3A molecular sieve, 4A molecular sieve and 5A molecular sieve, or a combination of at least two thereof; and / or The dehydrating agent B is one of Additive TI, Additive OF, dehydrating agent PTSI and dehydrating agent BF-5, or a combination of at least two of them. Preferably, the thixotropic agent in component A and component B has a specific surface area of 80 to 200 m 2 / g of hydrophobic fumed silica.
9. The method for preparing the wide temperature range heat-resistant two-component polyurethane thermally conductive structural adhesive for power battery PACK according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Preparation method of component A: put the formulated amount of bio-based polyol, polyol resin A, polyol resin B, catalyst, thixotropic agent, dehydrating agent A and thermal conductive filler into a double planetary stirring kettle in sequence, start vacuum degassing, use a high-speed disperser and a stirring paddle to stir for 40 minutes to 1.5 hours, and finally discharge the material to obtain component A; 2) Preparation method of component B: put the formulated amount of isocyanate-terminated polyurethane prepolymer, coupling agent, dehydrating agent B, thixotropic agent and thermal conductive filler into a double planetary stirring kettle in sequence, start vacuum degassing, use a high-speed disperser and a stirring paddle to stir for 40 minutes to 1.5 hours, and finally discharge the material to obtain component B. 3) The above-mentioned component A and component B are mixed evenly in a volume ratio of 1:(0.9-1.2) to obtain a two-component polyurethane thermal conductive structural adhesive.
10. Use of the wide temperature range heat-resistant two-component polyurethane thermally conductive structural adhesive for power battery PACK according to any one of claims 1 to 8 or the wide temperature range heat-resistant two-component polyurethane thermally conductive structural adhesive for power battery PACK prepared by the preparation method according to claim 9 in power battery PACK.
Citation Information
Patent Citations
Damp-heat-resistant polyurethane heat-conducting structural adhesive and preparation method thereof
CN115491159A
High-strength high-temperature-resistant two-component polyurethane heat-conducting structural adhesive and preparation method thereof
CN117887410A
Bi-component polyurethane foaming adhesive and preparation method thereof
CN109722206A
Conductive silver adhesive and preparation method and application thereof
CN112778948A
Heat-conducting two-component polyurethane adhesive and preparation method and application thereof
CN113999643A
Cited By
Polyurethane adhesive as well as preparation method and use method thereof
CN120442210A
A polyurethane adhesive and its preparation and application methods
CN120442210B